From fish to FISH: the comparative pathology of neuroblastomas in humans, mice and fish - Schwab, Manfred (Journal of cancer research and clinical oncology, 1999)
Neuroblastoma is a malignant cancer of the sympathetic nervous system and is one of the most frequent solid cancers in young children. Only a few of the many advances in our understanding of basic genetic and cellular mechanisms leading to neuroblastoma development have translated to clinical practice, and the prognosis for children with neuroblastoma, particularly at advanced stages, has remained poor. Major directions for neuroblastoma management and control include the application of prognostic parameters, particularly amplified MYCN, which can be readily visualized by chromosomal fluorescence in situ hybridization (FISH), for individual therapy design, as well as the initiation of a presymptomatic screening program for early tumor detection to reduce the fraction of advanced-stage tumors. In addition, new and innovative therapeutic approaches are being sought. The understanding of molecular and cellular pathways resulting in spontaneous regression in up to 10% of neuroblastoma patients, possibly by apoptosis, could provide the basis for new biologically based therapeutic interventions. Unlike most other pediatric cancers, neuroblastoma can be studied in two experimental animal systems. One is the fish system Xiphophorus, where neuroblastomas can be induced in specific strains by exposure to mutagens/carcinogens; the second is mice that carry MYCN as a transgene. These animal systems demonstrate that neuroblastomas are evolutionarily conserved tumors. Their study could well result in a better understanding of neuroblastoma development. At the same time they represent systems in which experimental therapies can be preclinically tested.